Case Report: Popliteal arterial tumor embolus as the initial presentation of EGFR-mutant lung adenocarcinoma with pulmonary-vein invasion - Hong, Yongchun; Ding, Xinjing; Ding, Jianghua (Frontiers in Oncology, 2025)
Thrombotic events represent a common complication and the second leading cause of mortality among patients with non-small cell lung cancer (NSCLC). Nonetheless, it is exceedingly rare for thrombosis to manifest initially in atypical locations, such as the popliteal artery, in individuals with NSCLC. In this report, we present a case involving an elderly patient with NSCLC who initially exhibited acute thrombosis of the popliteal artery in the left limb. The patient underwent a salvage arterial thrombectomy followed by a transfemoral amputation. Pathological examination revealed that the thrombus was a tumor embolus. A chest CT scan identified a mass in the right lower lung with a maximum diameter of 2.8 cm, along with multiple pulmonary nodules and a clot in the right inferior pulmonary vein. Pathological analysis of the lung mass confirmed the presence of lung adenocarcinoma, thereby verifying that the tumor embolus originated from NSCLC. The patient subsequently received treatment with osimertinib, resulting in partial remission. In instances of thrombosis occurring in uncommon sites, it is crucial to consider the potential for tumor thrombus.